Dynamics of VEGF-А, Аngiopoietin-2 and HIF-1α Levels in Patients with Brain Metastases Treated with Cyberknife Radiosurgery - Veselin Popov MD, PhD, MHM; Gabriela Raycheva MD, PhD; Zhanet Grudeva-Popova MD, PhD, MH (Technology in Cancer Research & Treatment)
Objectives : The contemporary concept of carcinogenesis summarizes the role of hypoxia, neoangiogenesis, and hemostasis, including in the stage of progression and metastasis of the tumor process. Metastatic disease is a serious therapeutic challenge for any oncological condition. The purpose of this study was to evaluate the dynamics of specific indicators of neoangiogenesis and hypoxia as potential biomarkers for therapeutic efficacy or risk of disease progression in patients with brain metastases (BM) undergoing robotic stereotactic radiosurgery. Methods: Two groups of patients (lung cancer and other types of cancers) with oligometastatic disease and brain metastases were included. The patients (n=66) were treated with CyberKnife system. Human Angiopoietin-2, Hypoxia inducible factor 1 α (HIF-1α) and human Vascular Endothelial Growth Factor-А (VEGF-А) were measured in this prospective longitudinal study. Results: Analysis of human Angiopoietin-2, HIF-1α, human VEGF-A in the post-treatment period showed a statistically significant decrease between the baseline and the 6 months post-treatment time point in both patient groups. The baseline value of serum VEGF-А in the group with lung cancer decreased by 40%, Аngiopoietin-2-by 48%, HIF-1α -by 43%. In the group with other types of cancers, VEGF-А decreased by 54.75%, Аngiopoietin-2-by 52%, HIF-1α -by 39.5%. Despite the significant reduction, the levels remained significantly higher in both groups than in healthy controls. Conclusion: This study underscores the potential of integrating molecular markers like VEGF-A, Angiopoietin-2, and HIF-1α into clinical decision-making to enhance outcomes for patients with brain metastases undergoing RSRS.